Selling into Industries: Technology Companies. - Lotardo, Elizabeth; Earle McLeod, Lisa (linkedin.com, 2018)
Learn how to sell to tech buyers who make decisions quickly. Find out how to adapt to current trends, connect with key financial metrics, and break through clutter to get noticed.